Survey on the clustering schemes of mobile ad-hoc Wireless Sensor Network (WSN) - Ahmed, Mushrif; Sarker, Rakesh (BRAC University, 2013)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2012.